The Effectiveness of the Use of Phakic Intraocular Lenses to Correct Myopia - S. A., Boboev (American Journal of Biomedicine and Pharmacy, 2025)
Myopia, or nearsightedness, is one of the most prevalent refractive errors worldwide and is increasing in incidence, particularly among young adults. While spectacles and contact lenses offer temporary correction, surgical approaches such as phakic intraocular lens (pIOL) implantation have emerged as long-term solutions for patients with high degrees of myopia who are not candidates for corneal refractive surgeries like LASIK due to thin corneas or other contraindications. This study aimed to evaluate the clinical efficacy, safety, and visual outcomes of posterior chamber phakic intraocular lens implantation in patients with moderate to high myopia. A prospective clinical investigation was conducted on 80 patients (160 eyes) aged 21–45 years with myopic refractive errors ranging from -6.0 D to -20.0 D. Patients were selected based on anterior chamber depth, endothelial cell density, and general ocular health. Visual acuity, refractive stability, intraocular pressure (IOP), endothelial cell count, and patient satisfaction were assessed preoperatively and postoperatively at regular intervals over a 12-month follow-up. The study demonstrated significant improvement in uncorrected visual acuity (UCVA), with 92% of eyes achieving 20/25 vision or better. There were no cases of significant endothelial cell loss, lens dislocation, or secondary glaucoma. These findings support the effectiveness of phakic intraocular lenses as a viable, reversible, and stable method of correcting myopia, particularly in cases where corneal refractive surgery is contraindicated.